COOPERATION AND CONFLICT – THE BRITISH ARMY, THE NATAL GOVERNMENT AND THE PROSECUTION OF NATAL REBELS DURING THE ANGLO-BOER WAR - Wassermann, Johan (Scientia Militaria - South African Journal of Military Studies, 2011)
The Natal Afrikaner rebels hardly feature in the historiography of the Anglo-Boer War of 1899–1902. The Times History of the War in South Africa dismisses their rebellion in one sentence, while the Natal Mercury of 25 April 1900 correctly points out that the number of rebels and the scale of the rebellion are rather insignificant when compared with that of the Cape Colony. In the latter, where in contrast to Natal, Afrikaners formed the bulk of the white population, the dynamics of the rebellion was very different. The large number of Afrikaners resident in the Cape Colony acted as a magnet for the Republican forces and as a result, large numbers of Afrikaners took up arms against Britain. From their side, the British authorities acted with a vengeance towards the Cape rebels, executing and imprisoning large numbers.